A conserved coccidian gene is involved in Toxoplasma sensitivity to the anti-apicomplexan compound, tartrolon E. (December 2020) - Bowden, Gregory D.; Reis, Patricia M.; Rogers, Maxwell B.; Bone Relat, Rachel M.; Brayton, Kelly A.; Wilson, Sarah K.; Di Genova, Bruno Martorelli; Knoll, Laura J.; Nepveux V, Felix J.; Tai, Albert K.; Ramadhar, Timothy R.; Clardy, Jon; et al.
Abstract: New treatments for the diseases caused by apicomplexans are needed. Recently, we determined that tartrolon E (trtE), a secondary metabolite derived from a shipworm symbiotic bacterium, has broad-spectrum anti-apicomplexan parasite activity. TrtE inhibits apicomplexans at nM concentrations in vitro, including Cryptosporidium parvum, Toxoplasma gondii, Sarcocystis neurona, Plasmodium falciparum, Babesia spp. and Theileria equi. To investigate the mechanism of action of trtE against apicomplexan parasites, we examined changes in the transcriptome of trtE-treated T. gondii parasites. RNA-Seq data revealed that the gene, TGGT1_272370, which is broadly conserved in the coccidia, is significantly upregulated within 4 h of treatment. Using bioinformatics and proteome data available on ToxoDB, we determined that the protein product of this t artrolon E r esponsive g ene ( trg ) has multiple transmembrane domains, a phosphorylation site, and localizes to the plasma membrane. Deletion of trg in a luciferase-expressing T. gondii strain by CRISPR/Cas9 resulted in a 68% increase in parasite resistance to trtE treatment, supporting a role for the trg protein product in the response of T. gondii to trtE treatment. Trg is conserved in the coccidia, but not in more distantly related apicomplexans, indicating that this response to trtE may be unique to the coccidians, and other mechanisms may be operating in other trtE-sensitive apicomplexans. Uncovering the mechanisms by which trtE inhibits apicomplexans may identify shared pathways critical to apicomplexan parasite survival and advance the search for new treatments. Graphical abstract: Image 1 Highlights: Tartrolon E is a broad-spectrum anti-apicomplexan compound. T. gondii responds to tartrolon E treatment by upregulating expression of the coccidian gene, trg. The gene product of trg has multiple transmembrane domains and is phosphorylated and thus may play a role in signaling. Deletion of trg results in an increase in parasite resistance to tartrolon E treatment.